Organoclay-filled PP/PBS polymer blends: Insights into morphology, thermal stability, and dielectric behavior - Taktak, Sirine; Ghorbel, Nouha; Fakhfakh, Slim; Rondot, Sébastien; Jbara, Omar; Arous, Mourad (Journal of Molecular Liquids, 2025)
Developing high-performance polymer blends from immiscible components such as polypropylene (PP) and polybutylene succinate (PBS) remains a significant challenge due to poor interfacial compatibility. In this study, we prepared intercalated nanocomposite films based on a PP/PBS: 80/20 blend reinforced with an organically modified montmorillonite (Cloisite 20, C20) using melt extrusion and compression molding. The aim was to investigate the effect of nanoclay incorporation on the structural, dielectric, thermal, and morphological properties of the blend. Broadband dielectric spectroscopy (BDS) was carried out over a frequency range of 0.1 Hz to 1 MHz and temperatures from 20 °C to 100 °C to analyze the molecular mobility and interfacial polarization mechanisms. Morphological, thermal, and chemical features were further characterized using scanning electron microscopy (SEM), differential scanning calorimetry (DSC), and fourier-transform infrared spectroscopy (FTIR). The SEM images revealed that the addition of C20 significantly modified the blend morphology, leading to reduce PBS nodules and improved dispersion. DSC results confirmed the nucleating role of C20 in enhancing the crystallization of both PP and PBS phases. These structural changes gave rise to distinct interfacial polarization processes: Maxwell–Wagner–Sillars (MWS) polarization at the PP/PBS interface and two additional interfacial polarizations (IPI and IPII) related to the nanoclay interactions with the polymer phases. The dielectric relaxation behavior was analyzed using the Havriliak–Negami model, revealing that the magnitude and position of the polarization processes strongly depend on the C20 content. The extracted activation energies further supported the impact of nanoclay on the molecular dynamics. Overall, this study demonstrates that incorporating Cloisite 20 nanoclay effectively tailors the interfacial structure and dielectric properties of PP/PBS blends, highlighting their potential for advanced applications in electrical insulation and functional polymer systems.
Keywords: Activation energies; Adhesion; Blends; Dielectric properties; Interface; Morphology; Nanoclay